answersLogoWhite

0

9y**2-25yz-6z**2

Multiply first and last terms

9*-6=-54

Find factors of -54

2,-27 = 2+-27=-25

-2,27 = -2+27=25

Rewrite

9y**2-27zy+2zy-6z**2

Factor pairs of terms

9y**2-27zy = 9y(y-3z)

2zy-6z**2= 2z(y-3z)

9y**2-27zy+2zy-6z**2= 9y(y-3z)+2z(y-3z)

Factor:

9y(y-3z)+2z(y-3z) = (y-3z)(9y+2z)

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake
BeauBeau
You're doing better than you think!
Chat with Beau
CoachCoach
Success isn't just about winning—it's about vision, patience, and playing the long game.
Chat with Coach

Add your answer:

Earn +20 pts
Q: What is 9y2 - 25yz - 6z2?
Write your answer...
Submit
Still have questions?
magnify glass
imp